Dietary folate intake and concentration of folate in serum and red blood cell in a group of female university students in Tehran, Iran - Bazhan, Marjan; Haghighian Roudsari, Arezoo; Shokouhi, Maryan; Mehran, Shiva; Ardestani, Hasan (Archives of Advances in Biosciences, 2013)
Adequate intake of folate has an important role in the prevention of nutritional anemia and other complications in childbearing age women. This study was undertaken to determine dietary folate intake and concentration of folate in serum and red blood cell (RBC) in female students of a medical university in Tehran, the capital of Iran. In this cross sectional study, 346 female students were randomly selected from students’ lists of eight schools at Shahid Beheshti University of Medical Sciences in Tehran, Iran. Those who were interested and eligible participated in this study. For each student, questionnaires about general characteristics were completed. Dietary folate intake was assessed by 3 days food recall questionnaire. These data were analyzed by Food Processor (FP). Folate in serum and RBC were determined by Radio Immunoassay (RIA). The results showed that mean age and body mass index in these students were 21.4±4.2 yrs and 22.2±3.2 kg/m2, respectively. Mean of 3 days folate intake was 239.4±101.8 µg/d. The majority of subjects (93%) did not meet the reference dietary intake for folate. Mean serum folate levels in whole population was 7.8±3.6 ng/ml and RBC folate was 249.6±124.9 ng/ml. No correlation was found between folate concentrations in serum and RBC with folate intake from food. The result of this study showed that folate intake of students is very low. Therefore, appropriate intervention is necessary for adequate intake of folate.